Design and implementation of an automatic control system applying pid in the positioning of an electric wheelchair - Zegarra Poma, Samuel (2025)
According to the World Health Organization (2018), a large part of the population requires a wheelchair to be able to mobilize and perform their daily activities. Conventional wheelchairs have been used for years to help the user to use them. However, it is believed that people's needs have evolved over the years and they are currently looking for something more in each product. So, what this project wants is to give the user more control over the angle, positions and height of the wheelchair seat to improve the quality of life of this person. The control will incorporate a manual drive system to control the movement and height of the chair and an automatic control applying a PID control with data obtained from an IMU as an input and its output is the voltage to drive the motor, which activates an electric piston that regulates the inclination of the wheelchair seat by 3 degrees, all this improves the quality of life of the person and makes the development of their activities more practical.